Menarche as maturational factor in young swimmers` development of morphological, physical and performance characteristics over a year of training - López-Plaza, D.; Alacid, F.; Abellán-Aynés, O.; Quero-Calero, C. D. (Medicine & Science in Sports & Exercise, 2025)
Purpose At the age of menarche, there is a significant increase in the secretion of sex hormones, affecting physical and morphological growth. This study aimed to investigate the impact of menarche on the development of body dimensions, fitness level, technical skills, and performance in pubertal female swimmers over 1 yr of training.